Secure message exchange using text to image encoding - Barik, Swastik; Manikanta Sai, J; Prasannanjaneyulu Reddy, Ch; Kalyan Chakravarthy, P (International Journal of Engineering and Technology, 2018)
The work focuses mainly on data security problems while transferring data through a network, using text-to-image encryption. This Â Â Â Â Â Â Â Â approach creates an image out of the textual data using steganography, which allows the sender and the intended recipient to hide their confidential data while transmitting through the network. First, binary representations of the text data are made, then the binary data is used to create an image by using it as pixel intensities. This image is then merged with a colour image to obtain the final encrypted image. The main objective of the work is to demonstrate an encryption scheme that is reliable and easy to implement.Â Â